2020
DOI: 10.3390/ijerph17238853
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Perceived Stress, Depression and Alcohol Use Disorders in University Students during the COVID-19 Pandemic: A Socio-Economic Dimension

Abstract: The objective of the study was to examine the effects of perceived stress on depression and subsequently to examine the effects of depression on alcohol use disorders. The data were obtained by an electronic questionnaire survey during the coronavirus disease 2019 (COVID-19) pandemic (n = 1523 Slovak university students). Descriptive, regression, and correlation analysis were used in the analytical processing, while the analyses included students’ scores in three diagnostic tools (Perceived Stress Scale (PSS),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 114 publications
4
26
0
2
Order By: Relevance
“…General medical problems secondary to alcohol consumption, acute and chronic toxicity of ethanol can affect the entire body [ 70 ]. The effects of alcohol on the brain are described below [ 71 , 72 , 73 ]: under the influence of alcohol, emotions can become exaggerated and the consumer is excessively happy, expansive or emotional alcohol has a depressing effect on the central nervous system, causing drowsiness, an effect dependent on the amount consumed; over time alcohol changes the architecture of sleep, decreasing periods of deep sleep and increasing the number of awakenings during the night on a short-term, alcohol has an anxiolytic effect, but the period of relaxation and mental comfort is short influences the pleasure centers (dopamine-mediated) and the reward system in the brain, which partly explains the installation of alcohol dependence acts on the production of opioid substances, which explains the analgesic effect affects the hippocampus, the area of ​​the brain where memory-related processes take place and so the consumer no longer remembers what he did during consumption and immediately afterwards inhibits the production of neurotransmitters, such as gamma-amino-butyric acid (GABA) and glutamate, the effect being to slow down the transmission of nerve impulses through the brain increased blood alcohol level over 0.05% causes disorders of nerve activity in the frontal lobe and thus difficulties in impulse control and decision making, decreased thought and judgment, reduced censorship the effect of alcohol on the cerebral amygdala causes consumers not to realize that certain actions of theirs can have dangerous effects and thus scandals, violence, accidents can occur the action of alcohol on the cerebellum leads to loss of balance, coordination of movements and instability of gait when the alcohol level exceeds 0.04%, the functioning of the reflex centers in the brainstem that control breathing, coughing, sneezing can be inhibited and they become unable to regulate the vital functions of the body, in extreme cases, death can occur[ 74 ]. …”
Section: Alcohol Consumption Psychological Imbalances and Covid-19mentioning
confidence: 99%
“…General medical problems secondary to alcohol consumption, acute and chronic toxicity of ethanol can affect the entire body [ 70 ]. The effects of alcohol on the brain are described below [ 71 , 72 , 73 ]: under the influence of alcohol, emotions can become exaggerated and the consumer is excessively happy, expansive or emotional alcohol has a depressing effect on the central nervous system, causing drowsiness, an effect dependent on the amount consumed; over time alcohol changes the architecture of sleep, decreasing periods of deep sleep and increasing the number of awakenings during the night on a short-term, alcohol has an anxiolytic effect, but the period of relaxation and mental comfort is short influences the pleasure centers (dopamine-mediated) and the reward system in the brain, which partly explains the installation of alcohol dependence acts on the production of opioid substances, which explains the analgesic effect affects the hippocampus, the area of ​​the brain where memory-related processes take place and so the consumer no longer remembers what he did during consumption and immediately afterwards inhibits the production of neurotransmitters, such as gamma-amino-butyric acid (GABA) and glutamate, the effect being to slow down the transmission of nerve impulses through the brain increased blood alcohol level over 0.05% causes disorders of nerve activity in the frontal lobe and thus difficulties in impulse control and decision making, decreased thought and judgment, reduced censorship the effect of alcohol on the cerebral amygdala causes consumers not to realize that certain actions of theirs can have dangerous effects and thus scandals, violence, accidents can occur the action of alcohol on the cerebellum leads to loss of balance, coordination of movements and instability of gait when the alcohol level exceeds 0.04%, the functioning of the reflex centers in the brainstem that control breathing, coughing, sneezing can be inhibited and they become unable to regulate the vital functions of the body, in extreme cases, death can occur[ 74 ]. …”
Section: Alcohol Consumption Psychological Imbalances and Covid-19mentioning
confidence: 99%
“…The prevalence of depression among college and university students under the COVID-19 pandemic varies depending on the diagnostic tools utilized, population in question, duration of quarantine/isolation, and how severely the areas in question have been affected [ 16 ]. However, in previous studies of college and university students using the PHQ-9, the following were the depression prevalence (PHQ-9 ≥10) rates reported: 46.5% in the UK [ 17 ], 9.0% in China [ 18 ], 18.5% in Slovakia [ 19 ], and 31.7% in Ukraine [ 20 ]. Although a direct comparison between countries is difficult, within Japan, a study [ 14 ] investigating the pre-pandemic situation among 2194 students at one national university reported a 28.7% prevalence of depression (95% CI, 27–31) based on PHQ-9 scores ≥5.…”
Section: Discussionmentioning
confidence: 99%
“…Although some specific instruments measure emotional well-being during quarantine, information on the psychometric properties of these scales is still scarce. We used the Perceived Stress Scale (PSS-10), modified for COVID-19 (PSS-10-C), because this instrument’s internal consistency is acceptable, as other studies have shown [ 28 , 29 , 30 , 31 ], and it has been employed in studies that measure students’ stress [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%